2003
DOI: 10.1016/j.cub.2003.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Differentiation Is Regulated by the Rho and ROCK Signaling Pathway

Abstract: The epidermis comprises multiple layers of specialized epithelial cells called keratinocytes. As cells are lost from the outermost epidermal layers, they are replaced through terminal differentiation, in which keratinocytes of the basal layer cease proliferating, migrate upwards, and eventually reach the outermost cornified layers. Normal homeostasis of the epidermis requires that the balance between proliferation and differentiation be tightly regulated. The GTP binding protein RhoA plays a fundamental role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 20 publications
10
107
0
Order By: Relevance
“…53 ROCK family members stimulate the ordering of the actin cytoskeleton (ROCKI) and terminal keratinocyte differentiation (ROCKII). 25,28 The expression pattern of Bcl-2 family members changes upon keratinocyte differentiation. Their role is not related to skin differentiation as such, but they participate in the control of cellular integrity upon exposure of the skin to damaging agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 ROCK family members stimulate the ordering of the actin cytoskeleton (ROCKI) and terminal keratinocyte differentiation (ROCKII). 25,28 The expression pattern of Bcl-2 family members changes upon keratinocyte differentiation. Their role is not related to skin differentiation as such, but they participate in the control of cellular integrity upon exposure of the skin to damaging agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK inhibition also results in inhibition of keratinocyte terminal differentiation and an increase in keratinocyte proliferation. 28 Accordingly, ROCKII activation induced cell cycle arrest and the expression of terminal differentiation markers. These results indicate that ROCK plays a critical role in regulating the balance between proliferation and differentiation in human keratinocyte cultures.…”
Section: Cytoskeleton Rearrangementsmentioning
confidence: 99%
“…In addition to the MAPK family of kinases, other candidate kinases can also regulate keratinocyte behavior (19,20). Accordingly, we next examined the extent to which Rho signaling may be involved in mediating MT1-MMP-induced pheno- A, SCC25-tet-V (V) and SCC25-tet-MT (MT) cells were plated overnight in serum-containing media, serum-starved for 24 h, and then treated with doxycycline (Dox, 2 g/ml) for 24 h. The cells were then analyzed for ␣2-␣3-, and ␤1-integrin expression by FACS analysis.…”
Section: Mt1-mmp-induced Cellular Aggregation Is Mediated By Rock1/2 mentioning
confidence: 99%
“…typic changes by using two well characterized and frequently used inhibitors (H1191 and Y27632) to block the activity of the Rho-associated kinases ROCK1 and ROCK2. ROCK1 and ROCK2 are the best-characterized downstream Rho effectors (53,54) and have been shown to play a role in the regulation of cell-cell and cell-matrix interaction (19,20). SCC25-tet-V and SCC25-tet-MT cells were pretreated with H1191 and co-treated with doxycycline.…”
Section: Mt1-mmp-induced Cellular Aggregation Is Mediated By Rock1/2 mentioning
confidence: 99%
“…Skin Development and Maintenance-Mutant overexpression and inhibitor studies in cultured keratinocyte cell lines have shown that RhoA signaling is essential for regulating skin cell proliferation and differentiation (17) and cell-cell contacts (18). Different from that in MEF cells (12), keratin-5 Cre-driven rhoA deletion in keratinocytes in vivo was sufficient to reduce phosphorylation of MLC and cofilin (19).…”
Section: Signaling Role Of Rhoa Revealed By Gene Targeting In Micementioning
confidence: 99%